An analysis of student performance in Chicago's charter schools - Myron Orfield; Thomas Luce (Arizona State University, 2016)
Charter schools have become the cornerstone of school reform in Chicago and in many other large cities. Enrollments in Chicago charters increased by more than ten times between 2000 and 2014 and, with strong support from the current mayor and his administration, the system continues to grow. Indeed, although state law limits charter schools in Chicago to 75 schools, proponents have used a loophole that allows multiple campuses for some charters to bypass the limit and there are now more than 140 individual charter campuses in Chicago. This study uses comprehensive data for the 2012-13 and 2013-14 school years to show that, after controlling for the mix of students and challenges faced by individual schools, Chicago's charter schools underperform their traditional counterparts in most measurable ways. Reading and math pass rates, reading and math growth rates, graduation rates, and average ACT scores (in one of the two years) are lower in charters all else equal, than in traditional neighborhood schools. The results for the two years also imply that the gap between charters and traditionals widened in the second year for most of the measures. The findings are strengthened by the fact that self-selection by parents and students into the charter system biases the results in favor of charter schools.